2010
DOI: 10.1021/jm100060b
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of (2,4-Dihydroxy-5-isopropylphenyl)-[5-(4-methylpiperazin-1-ylmethyl)-1,3-dihydroisoindol-2-yl]methanone (AT13387), a Novel Inhibitor of the Molecular Chaperone Hsp90 by Fragment Based Drug Design

Abstract: Inhibitors of the molecular chaperone heat shock protein 90 (Hsp90) are currently generating significant interest in clinical development as potential treatments for cancer. In a preceding publication (DOI: 10.1021/jm100059d ) we describe Astex's approach to screening fragments against Hsp90 and the subsequent optimization of two hits into leads with inhibitory activities in the low nanomolar range. This paper describes the structure guided optimization of the 2,4-dihydroxybenzamide lead molecule 1 and details… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
171
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 237 publications
(178 citation statements)
references
References 62 publications
6
171
0
1
Order By: Relevance
“…AT13387 is a novel small molecule inhibitor of HSP90 that was discovered with a fragment-based drug discovery approach that has been described in detail elsewhere. (32) X-ray crystallographic analysis of AT13387 in complex with the N-terminal domain of HSP90 showed that it bound within the N-terminal ATPase catalytic site and overlapped with the binding site for ATP. (32) Direct binding of AT13387 to HSP90 was investigated with isothermal calorimetry.…”
Section: Resultsmentioning
confidence: 99%
“…AT13387 is a novel small molecule inhibitor of HSP90 that was discovered with a fragment-based drug discovery approach that has been described in detail elsewhere. (32) X-ray crystallographic analysis of AT13387 in complex with the N-terminal domain of HSP90 showed that it bound within the N-terminal ATPase catalytic site and overlapped with the binding site for ATP. (32) Direct binding of AT13387 to HSP90 was investigated with isothermal calorimetry.…”
Section: Resultsmentioning
confidence: 99%
“…To date, there are 13 new Hsp90 inhibitors at various stages of clinical development (5)(6)(7)(9)(10)(11)(12)(13)(14)(15)(16)(17). The earlier geldanamycin analogues (i.e., 17-AAG or 17-DMAG), despite potent in vitro and in vivo preclinical activity, have not shown clear clinical benefit (5,31).…”
Section: Discussionmentioning
confidence: 99%
“…NVP-HSP990 is highly potent and selective for Hsp90 and represents one of the most potent oral Hsp90 inhibitors reported (5)(6)(7)(9)(10)(11)(12)(13)(14)(15)(16)(17). The GTL-16 model was selected as a screening model due to its growth and survival dependency on the Hsp90 client protein c-Met (24).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations